Perkembangan Teknologi Komunikasi: Perspektif Komunikasi Peradaban - Saefudin, Asep (FIkom Unisba, 2008)
The word of technology was derived from technique and logos, means knowledge about methods or doing something (technical term). Technology refered to how-to-do an act or product. In Greek language, technology means ’techne’ or ’art’, or ’skill’. In term of specified meaning, technology refer to industrial process which leads to skills in performing an activity. In broad meaning, technology refer to the whole process of materials. Communication technology is differentiated from information technology. Communication technology was utilized for conducting any kind of message transmission, from the act of sending to receiving. Whereas information technology is concerning managing and collecting information. It is hard to differentiate communication and information technology due to technology convergence. Both information and communication technology, as a term, are freely exchanging today because in every communication, there’s always be information as well.